Blood pressure patterns and body mass index status in pregnancy: An assessment among women reporting for antenatal care at the Korle-Bu Teaching hospital, Ghana. - Mary Amoakoh-Coleman; Deda Ogum-Alangea; Emefa Modey-Amoah; Michael Yao Ntumy; Richard M Adanu; Samuel A Oppong (PLoS ONE, 2017)
Maternal obesity in pregnancy has been linked with increased risk of pregnancy induced hypertension (PIH). In some tertiary referral hospitals in Ghana, PIH is the leading cause of institutional maternal mortality.To evaluate blood pressure changes during pregnancy amongst different body mass index (BMI) groups and how this relates to the risk of developing PIH.Women who had a dating ultrasound before 20 weeks gestation and registering for antenatal care at the Korle-Bu Teaching Hospital in Accra, between February and December 2013 and met the inclusion criteria were recruited into a cohort study. BMI was assessed at baseline. Blood pressure measurements were taken at (±2) 24, 28 and 36 weeks. Primary outcome measure of interest during follow-up was a diagnosis of PIH at these points. BP changes during follow up at the three points were measured. Descriptive analysis of baseline factors was carried out and compared for the BMI groups. Relative risk (RR) of PIH was estimated at 95% confidence interval.Mean (SD) age for the 361 women was 30.9 (4.8) years. Incidence of PIH amongst the cohort was 10.5% (95% CI: 7.45% - 14.45%) and 40.4% and 33.0% of them were overweight and obese respectively at baseline. Pregnant women who were obese at baseline had a three-fold increased risk of PIH compared to those with normal BMI [RR = 3.01 (1.06-8.52), p = 0.04].Obese women have a significantly increased risk of PIH. Women should be screened at booking for obesity status. Antenatal protocols should have interventions for prevention or early detection of obesity and management of obesity to improve outcomes.